Umumta‘lim maktablarida basketbol sport seksiyasiga tanlashda xalq harakatli o‗yinlardan foydalanish samaradorligi - Kdirova, M.A; Omirzakov, O.P (SCIENCE and SOCIETY, 2023)
In the article, students of general education schools, their extracurricular activities were selected as the object of re- search. The process of circle training was analyzed on the example of basketball.
Keywords: physical education; pedagogy; sports; basketball; action games